(untitled) (Cardiovascular Journal, 2017)
Background: The changes in serum creatinine level after Percutaneous coronary Intervention has been reported by different authors. Methods: Total 87 (Male71: Female 16) patients were enrolled in this very preliminary study who underwent elective PCI and has normal serum creatinine level. Total 116 stents were deployed in 108 territories. Mean age for both male : female were (55: 58) yrs. Associated CAD risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking (all male). Results: Among the study group; 65(74.3%) were Dyslipidemic, 74(85%) were hypertensive; 52(58%) patients were Diabetic, FH 12(13.8%), Hypothyroid 3(3.4%) and 30(42.3%) were all male smoker. Female patients were more obese (BMI: M 25: F 28). Average uses of contrast material was 81 ml. Serum Creatinine level was pre-procedural male: female (1.35: 1.44) and post-procedural 2nd day for male: female were (1.24: 1.45). Common stented territory was LAD 48(44.4%), RCA 41(38%), and LCX 19(17.6%). Stent used were all DES. Among them, Everolimus eluting stents 69 (70.4%), Sirolimus Eluting stents 22(22.4%) and Biolimus Eluting stents 7 (7.1%). Conclusion: In the current prospective non randomized study, we found that the cautious injection of Iodinated contrast doesnt change post procedural s. creatinine level at 2nd day-of PCI. Cardiovasc. j. 2017; 9(2): 155-158